Students’ Perception and Experience of Ghost Writing – Study with Reference to Mangalore City - Venkatesha Nayak; Kavya P Hegde (Indonesian Journal Of Educational Research and Review, 2022)
Higher education in India is vibrant as it assumes greater role interns of building the nation. As enrolment ratio is less, Govt through Universities and colleges promote higher education and the reach is now in rural areas too. To enrol more number of the students has become a target for the colleges and faculties’ working there, as a result to increase the quantity, less attention is paid towards the quality of higher education. The higher education is associated with the tasks such as assignment writing, dissertations to full fill the requirements of the particular degree and these are graded to improve the research habits among the students and at the same time to enhance the quality of higher education which also contribute for the development of certain skills among student community. There are agencies and individual involved to assist the students by providing the service of writing the assignments and dissertations for certain prescribed amount of money. There are academic writers (Ghost writers) who provide such readymade assignments and dissertations to the students. In this paper attempt is done to find the students perception and at the same time their experiences of ghost writers are studied. The study is concentrated in Mangalore city of Karnataka State students those who perused higher education and undergone dissertation while perusing their master degree.